Assessing the Prevalence and Impact of Depression in Alzheimer's Disease: A Comparative Psychometric Analysis and Patient Outcomes. A comparative Scale Efficacy Analysis and Patient Outcomes (Medical Forum Monthly, 2024)
Objective: The objective of this study was to evaluate the rate of depression in Alzheimer’s patients with dementia, to evaluate the inter-rater reliability of the CSDD, and also to compare depression scores between the CSDD and GDS tools.Study Design: A cross-sectional descriptive study.Place and Duration of Study: This study was conducted at the Institute of Psychiatry, Benazir Bhutto Hospital, Pakistan fro m January 2023 to September 2023.Methods: A cross-sectional descriptive survey was conducted on 45 patients diagnosed with Alzheimer's (dementia). The cognitive status of the participants was evaluated using the MMSE, while the participants’ depression status was evaluated using the CSDD and GDS.Results: The study included 45 patients with Alzheimer’s disease, with a mean age of 73.5 years. The average time duration between the onset of the symptoms and diagnosis of the disease was 7.8 years. By administering Geriatric Depression Scale (GDS) the results showed that 57.8% of the patients had mild levels of depressive symptoms. While 86.4% of patients had probable major depression on informant rating, and 84% on patient ratings on the scale. When comparing the totals obtained with the GDS and the CSDD, it was found that the CSDD classified a higher number of patients as having probably major depression than did the GDS, therefore suggesting, that the CSDD could be a more sensitive instrument in detecting depressive symptoms in Alzheimer’s patients than GDS. Patient-informant concordance on CSDD was confirmed with a correlation coefficient of 0.804 (p < 0.01) based on Kendall’s Tau Correlation. Hence provided evidence that both informant and patient ratings are correlated and reliable.Conclusion: Alzheimer’s patients comprise elderly persons who are most likely to have dementia and depression. This study's results align with previous study findings and confirm that CSDD is a better tool to assess depression among dementia patients as compared to GDS.